Market Communication in the COVID-19 Pandemic: Case Study Based on The Analysis of a Single Actor from The Tourism Sector - Barbara MARCISZEWSKA; Marzena WANAGOS (Communications of International Proceedings, 2021)
Tourism activities in 2020 and 2021 are marked by the specificity of communication in the sector, which still suffers from the administrative constraints imposed in connection with the COVID-19 pandemic. Many expected products are not present in the tourism offer because tourism enterprises have been forced by COVID-19 to close their market activity or to limit sales (e.g. airlines). This situation requires tourism enterprises to change the forms and content of market communication. A dialog between a tourism enterprise and a customer requires knowledge and experience exchange. This aspect has to be recognized a priori to be placed on the market with the tourism product. However, COVID-19 forces enterprises to respond to its impact on the socio-economic life, often limiting the possibility of recognizing pandemic consequences a priori. The study aims to present selected aspects of market communication and behaviours of a single actor from the tourism sector in Poland in uncertainty caused by COVID-19 limitations. This study discusses diversity in behaviours of the tourism enterprise in the environment and factors shaping marketing communication. The research problem results from the fact that most tourism products require modification during the time of COVID-19. This imposes a differentiation of marketing communication due to the specific circumstances. Desk research and entity observation were applied for resolving the research problem: How to change market communication in the COVID-19 pandemic to retain customers? The case study presents the difference in marketing communication in the COVID-19 period.
Keywords: Market Communication; COVID-19 Pandemic; Change of Communication; Analysis of The Single Actor